Significantly Promoting the Photogenerated Charge Separation by Introducing an Oxygen Vacancy Regulation Strategy on the FeNiOOH Co‐Catalyst. Issue 20 (17th April 2022) - Zhang, Rongfang; Ning, Xingming; Wang, Ze; Zhao, Huihuan; He, Yaorong; Han, Zhengang; Du, Peiyao; Lu, Xiaoquan
Abstract: Semiconductor/co‐catalyst coupling is considered as a promising strategy to enhance the photoelectrochemical (PEC) conversion efficiency. Unfortunately, this model system is faced with a serious interface recombination problem, which limits the further improvement of PEC performances. Here, a FeNiOOH co‐catalyst with abundant oxygen vacancies on BiVO4 is fabricated through simple and economical NaBH4 reduction to accelerate hole transfer and achieve efficient electron–hole pair separation. The photocurrent of the BV (BiVO4 )/Vo‐FeNiOOH system is more than four times that of pure BV. Importantly, the charge transfer kinetics and charge carrier recombination process are studied by scanning photoelectrochemical microscopy and intensity modulated photocurrent spectroscopy in detail. In addition, the oxygen vacancy regulation proposed is also applied successfully to other semiconductors (Fe2 O3 ), demonstrating the applicability of this strategy. Abstract : Herein, a FeNiOOH co‐catalyst with abundant oxygen vacancies on BiVO4 photoanode is fabricated through simple and economical NaBH4 reduction to accelerate hole transfer and achieve efficient electron–hole pair separation.